2019
DOI: 10.1111/arcm.12485
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of strontium to the human diet from querns and millstones: an experiment in digestive strontium isotope uptake

Abstract: The question of whether rock grit ingested unintentionally from querns, metates or millstones, or deliberately through pica or geophagy, is bioaccessible in the human gut has not been addressed in archaeological strontium (Sr) isotope studies. This study employed the unified bioaccessibility method and determined that ingested rock grit can provide bioaccessible 87 Sr/ 86 Sr, but that unintentional consumption is unlikely to constitute > 1% of the diet (by mass) and will not significantly change, that is, by >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Beyond isoscape mapping, variations in plant 87 Sr/ 86 Sr with root depth could have implications for the reconstruction of human and animal mobility patterns in archaeology. Humans make choices about what they consume and when and where they source those foods, and are thus not passive recipients of environmental strontium (Johnson et al, 2019). Furthermore, while it has been long known that strontium inputs are normalized to dietary calcium budgets (e.g., Comar, 1963), the influence of dietary composition on 87 Sr/ 86 Sr in humans has received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond isoscape mapping, variations in plant 87 Sr/ 86 Sr with root depth could have implications for the reconstruction of human and animal mobility patterns in archaeology. Humans make choices about what they consume and when and where they source those foods, and are thus not passive recipients of environmental strontium (Johnson et al, 2019). Furthermore, while it has been long known that strontium inputs are normalized to dietary calcium budgets (e.g., Comar, 1963), the influence of dietary composition on 87 Sr/ 86 Sr in humans has received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Radiocarbon dating of a sample of stratigraphically unassociated remains from the linear mortuary structure estimates that they date to between 3760-3660 cal BC (95 per cent probability; Griffiths, 2011: 85). (Johnson et al, 2019). Clays associated with coal measures give bioavailable values between 0.7095 and 0.7113 (n = 10).…”
Section: Isotope Constraints On Location and Surrounding Areamentioning
confidence: 99%
“…The Carboniferous limestone is well defined in terms of biosphere value, giving a plant interquartile range of 0.7090–0.7098 (n = 22). The gritstones that crop out in the Pennines give biosphere values between 0.7107 and 0.7114 (n = 11); a recent study which determined the bio-accessible Sr isotope composition from the Millstone Grit gives a value of 0.7115 (Johnson et al, 2019). Clays associated with coal measures give bioavailable values between 0.7095 and 0.7113 (n = 10).…”
Section: Isotope Constraints On Location and Surrounding Areamentioning
confidence: 99%
“…Knudson et al (2014) also found that archeological human and faunal samples were consistently offset from soil 87 Sr/ 86 Sr in many locations. This makes sense since soils and rocks are generally not directly consumed, although rock contributions to the diet might be nominal in groups that process food with grinding stones (Johnson et al, 2019), practice geophagy, or consume geological materials as digestive aids-all were done in the ancient Andes (Johns, 1990). These inconsistencies between bedrock, soil, and skeletal 87 Sr/ 86 Sr could be due to differential weathering of bedrock throughout the steep Andes and/or the overall paucity of bedrock and soil samples from the region; nonetheless, this illustrates the need for a deeper examination of different substrates for the analysis of bioavailable Sr in the region.…”
Section: Strontium Isotopes In the Andes: From Dietary Catchments To mentioning
confidence: 99%